THE USE OF IMMUNOSTIMULANTS FROM PAPAYA LEAVES TO TREAT DISEASE AND INCREASE NON-SPECIFIC IMMUNITY IN FISH AND SHRIMP - Muahiddah, Nuri; Diamahesa, Wastu Ayu (Journal of Fish Health, 2023)
The use of immunostimulants from papaya leaves as a treatment strategy for fish diseases has gained attention in the field of aquaculture. Initial studies have shown that the active compounds in papaya leaves have the potential as immunostimulants to enhance the fish immune system and combat disease infections. Previous studies have revealed that the administration of papaya leaf extracts in fish feed can stimulate immune responses, including activating immune cells such as macrophages and increasing antibody production. The compounds in papaya leaves also exhibit antimicrobial effects that help fight against pathogens causing diseases in fish. Although research findings indicate the potential use of papaya leaf immunostimulants, further studies are needed to understand their mechanisms of action comprehensively. Factors such as effective dosage, optimal administration methods, and their effects on various diseases must be clarified. Safety aspects should also be considered, including potential side effects and residues in fish intended for human consumption. Consideration should also be given to sustainable fish farming practices and the potential environmental impacts of the widespread use of papaya leaf immunostimulants. In conclusion, using immunostimulants from papaya leaves to treat fish diseases shows promising potential. However, further research is required to understand their effects thoroughly, determine the appropriate dosage, evaluate the safety, and consider sustainable aquaculture aspects before their use can be widely recommended in aquaculture practices.